2020
DOI: 10.1140/epjc/s10052-020-08573-9
|View full text |Cite
|
Sign up to set email alerts
|

Constraining visible neutrino decay at KamLAND and JUNO

Abstract: We study visible neutrino decay at the reactor neutrino experiments KamLAND and, JUNO. Assuming the Majoron model of neutrino decay, we obtain constraints on the couplings between Majoron and neutrino as well as on the lifetime/mass of the most massive neutrino state i.e., $$\tau _{3} / m_{3}$$ τ 3 / m 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…For different studies on visible neutrino decay at current or future experiments, we refer to Refs. [300][301][302][303][304][305][306].…”
Section: Introductionmentioning
confidence: 99%
“…For different studies on visible neutrino decay at current or future experiments, we refer to Refs. [300][301][302][303][304][305][306].…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [62], the authors discuss the visible neutrino decay for reactor experiments KAMLAND and JUNO. For visible decay of the astrophysical neutrinos at IceCUBE, see ref.…”
Section: Introductionmentioning
confidence: 99%
“…[27] found that DUNE will have a sensitivity of τ 3 /m 3 ≥ 4.27 × 10 −11 s/eV at 90% C.L.. Studies regarding visible neutrino decay, such as those considered in Ref. [28] constraint in the inverted ordering for both KamLAND and JUNO the lifetime of τ 2 /m 2 ≥ 1.4 × 10 −9 s/eV at 90% C.L. and in the normal mass ordering for JUNO τ 3 /m 3 ≥ 1.0 × 10 −10 s/eV at 90% C.L..…”
Section: Neutrino Lifetimementioning
confidence: 99%
“…In the case of active neutrinos, lifetime bounds can be quite different depending on the neutrino mass ordering, if it is normal or inverted, see e.g. [28].…”
Section: Strongmentioning
confidence: 99%
See 1 more Smart Citation